Effects of menstrual cycle on hemodynamic and autonomic responses to central hypovolemia - Shankhwar, Vishwajeet; Urvec, Janez; Steuber, Bianca; Schmid Zalaudek, Karin; Saloň, Adam; Hawliczek, Anna; Bergauer, Andrej; Aljasmi, Khawla; Abdi, Asrar; Naser, Asmaa; Himeidi, Maya; Alsuwaidi, Hanan; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background Estrogen and progesterone levels undergo changes throughout the menstrual cycle. Existing literature regarding the effect of menstrual phases on cardiovascular and autonomic regulation during central hypovolemia is contradictory. Aims and study This study aims to explore the influence of menstrual phases on cardiovascular and autonomic responses in both resting and during the central hypovolemia induced by lower body negative pressure (LBNP). This is a companion paper, in which data across the menstrual phases from healthy young females, whose results are reported in Shankwar et al. (2023), were further analysed. Methods The study protocol consisted of three phases: (1) 30 min of supine rest; (2) 16 min of four LBNP levels; and (3) 5 min of supine recovery. Hemodynamic and autonomic responses (assessed via heart rate variability, HRV) were measured before-, during-, and after-LBNP application using Task Force Monitor® (CNSystems, Graz, Austria). Blood was also collected to measure estrogen and progesterone levels. Results In this companion paper, we have exclusively assessed 14 females from the previous study (Shankwar et al., 2023): 8 in the follicular phase of the menstrual cycle (mean age 23.38 ± 3.58 years, height 166.00 ± 5.78 cm, weight 57.63 ± 5.39 kg and BMI of 20.92 ± 1.96 25 kg/m2) and 6 in the luteal phase (mean age 22.17 ± 1.33 years, height 169.83 ± 5.53 cm, weight 62.00 ± 7.54 kg and BMI of 21.45 ± 2.63 kg/m2). Baseline estrogen levels were significantly different from the follicular phase as compared to the luteal phase: (33.59 pg/ml, 108.02 pg/ml, respectively, p < 0.01). Resting hemodynamic variables showed no difference across the menstrual phases. However, females in the follicular phase showed significantly lower resting values of low-frequency (LF) band power (41.38 ± 11.75 n.u. and 58.47 ± 14.37 n.u., p = 0.01), but higher resting values of high frequency (HF) band power (58.62 ± 11.75 n.u. and 41.53 ± 14.37 n.u., p = 0.01), as compared to females in the luteal phase. During hypovolemia, the LF and HF band powers changed only in the follicular phase F(1, 7) = 77.34, p < 0.0001 and F(1, 7) = 520.06, p < 0.0001, respectively. Conclusions The menstrual phase had an influence on resting autonomic variables, with higher sympathetic activity being observed during the luteal phase. Central hypovolemia leads to increased cardiovascular and autonomic responses, particularly during the luteal phase of the menstrual cycle, likely due to higher estrogen levels and increased sympathetic activity.